2007
DOI: 10.1086/512060
|View full text |Cite
|
Sign up to set email alerts
|

On the Magnetic Flux Budget in Low‐Corona Magnetic Reconnection and Interplanetary Coronal Mass Ejections

Abstract: We present the first quantitative comparison between the total magnetic reconnection flux in the low corona in the wake of coronal mass ejections (CMEs) and the magnetic flux in magnetic clouds (MCs) that reach 1 AU 2Y3 days after CME onset. The total reconnection flux is measured from flare ribbons, and the MC flux is computed using in situ observations at 1 AU, all ranging from 10 20 to 10 22 Mx. It is found that for the nine studied events in which the association between flares, CMEs, and MCs is identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
348
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(389 citation statements)
references
References 102 publications
(130 reference statements)
36
348
3
2
Order By: Relevance
“…Following our discussion on the formation of the dimmings for this event via secondary reconnections with the surrounding fields, it is therefore not possible to directly compare the flux in the MC to the flux in the dimmings. Qiu et al (2007) have computed the flux swept out by flare ribbons for this event and found a value of (18.8 ± 1.8) × 10 21 Mx, which is in good agreement with the total MC flux.…”
Section: Overview Of Three Events With Different Characteristicssupporting
confidence: 68%
See 1 more Smart Citation
“…Following our discussion on the formation of the dimmings for this event via secondary reconnections with the surrounding fields, it is therefore not possible to directly compare the flux in the MC to the flux in the dimmings. Qiu et al (2007) have computed the flux swept out by flare ribbons for this event and found a value of (18.8 ± 1.8) × 10 21 Mx, which is in good agreement with the total MC flux.…”
Section: Overview Of Three Events With Different Characteristicssupporting
confidence: 68%
“…This indicates that the ejected rope was mostly formed by magnetic reconnection during the eruption process. Qiu et al (2007) found a different result concerning the flux in coronal dimming regions. These authors concluded that the flux in dimming regions is comparable in order of magnitude to the axial MC flux.…”
Section: Discussionmentioning
confidence: 89%
“…However, much of this flux is added to the rope by reconnection after the launch of the CME (Qiu et al 2007). Therefore, these observations do not provide conclusive evidence of the partition between axial and poloidal flux in the rope at the onset of the eruption.…”
Section: Magnetic Flux Budgetmentioning
confidence: 99%
“…Webb et al 2000;Mandrini et al 2005;Attrill et al 2006;Jian et al 2006). However, the erupting stucture is strongly modified by magnetic reconnection that occurs in the current sheet under the rising flux rope and produces the post-eruption flare arcade (e.g., Qiu et al 2007). We rather use flux cancellation in the active region to study the flux content of the structure before the eruption onset.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies of rapid reconnection during flares, in particular those using the evolution of flare ribbons overlaid on cotemporal magnetograms (Forbes and Priest, 1984;Poletto and Kopp, 1986;Fletcher and Hudson, 2001;Qiu et al, 2002;Qiu et al, 2007;Longcope et al, 2007;Qiu, 2009;Longcope et al, 2010;Kazachenko et al, 2010;Kazachenko et al, 2012), are the most direct antecedents of the present study. These two-ribbon flares generally follow the standard CSHKP flare model (See Priest and Forbes, 2002 for a review).…”
Section: Introductionmentioning
confidence: 72%